Lightweight Al-stabilized MgB2 conductor made by the IMD process. (19th September 2017) - Kováč, P; Hušek, I; Melišek, T; Kulich, M; Rosová, A; Kováč, J; Kopera, L; Balog, M; Krížik, P; Orovčík, Ľ
Abstract: Light single-core MgB2 wire stabilized by a unique Al–Al2 O3 metal matrix composite (MMC) was fabricated by the internal magnesium diffusion (IMD) process. Mg/B/Ta/Al–Al2 O3 composite was cold-deformed into a wire with a cross section of ∼1 mm, and finally heat-treated at temperatures of 635 °C–645 °C for times of 8–60 min. Critical temperatures and critical currents were evaluated by transport and magnetic measurements. Thermal stability and AC loss were characterized by the quench power from I –V curves and by the hysteresis loss measured by a calibration-free method. The results obtained clearly confirmed that the Al–Al2 O3 MMC mechanically supports the Mg/B/Ta wire core well during cold-working operations and subsequent heat treatment to form MgB2, while at the same time it retains its advantageous mechanical properties, and it can be utilized as a material for the outer sheath of MgB2 superconductors. Critical temperatures and critical current densities of MgB2 /Ta/Al–Al2 O3 are comparable with the values for other superconductors with MgB2 core fabricated by the IMD process using different sheath materials. The composition presented here shows promising potential for future lightweight and thermally stable superconducting MgB2 wires with high engineering current density.